Dinamika Kepemimpinan Pesantren Musthafawiyah Purba Baru Pasca Syekh Musthafa Husein Al-Mandili 1955-2003 - Seri Hartati Lubis; Abdul Salam (Jurnal Kronologi, 2023)
“The Dynamics of Leadership of the New Ancient Mustafawiyah Islamic Boarding School after Sheikh Musthafa Husein Al-Mandili 1955-2003 is the study discussed in this study. This study aims to find out the general description of Islamic boarding schools, the role of Sheikh Musthafa Husein in establishing Islamic boarding schools and to find out who the names of Sheikh Musthafa Husein Al-Mandili's generation are who continue the leadership relay at the Purba Baru Musthafawiyah Islamic Boarding School. The research was conducted in August 2022. The research method used is a historical research method which has four parts, including data collection (heuristics), source criticism, interpretation and writing (historiography). The Dynamics of Islamic Boarding School Leadership. Musthafawiyah Purba Baru, Mandailing Regency Natal after the death of Sheikh Mustafa Husein Al-Mandili, who was the founder of the Islamic Boarding School. During the leadership of H. Abdullah Musthafa, the changes and developments of Islamic boarding schools were very advanced in the physical field and were very well known not only in North Sumatra Province, but also in other provinces such as West Sumatra, Riau, Jambi, Bengkulu, Aceh and so on. After he died in 1995, his leadership was continued by his son, H. Musthafa Bakri. Then the leadership was taken over by his uncle, Drs. H. Abdul Khalik. This causes chaos that results in discord between families. Drs. H. Abdul Khalik in managing the Musthafawiyah Islamic Boarding School caused many problems that were very detrimental to the Pesantren, where in his leadership there were many disputes on the part of the family, students, and teachers.